1994
DOI: 10.1093/rheumatology/33.2.109
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies to Myeloperoxidase in Idiopathic and Drug-Induced Systemic Lupus Erythematosus and Vasculitis

Abstract: Circulating antibodies to myeloperoxidase (MPO) have been described in a variety of vasculitic syndromes, drug-induced SLE and drug-induced nephritis. We have examined the autoantibody profile in acute sera from patients with antineutrophil cytoplasmic antibody-positive vasculitis (n = 8), drug-induced nephritis (n = 4), drug-induced lupus (n = 7), SLE (n = 27) and nephritis-associated with SLE (n = 17). Significant binding to purified MPO in ELISA was given by all sera from patients with vasculitis and drug-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 0 publications
2
57
0
Order By: Relevance
“…In LN, the prevalence of ANCA is reported to be about 46% (45/99 cases) [1,13]. In our study, the prevalence of ANCA in LN was similar to the previous reports.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In LN, the prevalence of ANCA is reported to be about 46% (45/99 cases) [1,13]. In our study, the prevalence of ANCA in LN was similar to the previous reports.…”
Section: Discussionsupporting
confidence: 91%
“…It is highly associated with drug-induced SLE [5,13], serositis [3] or dermal vasculitis [17]. But until now, its relationship to renal involvement is not clear.…”
Section: Clinical Implications Of Antineutrophil Cytoplasmic Antibodymentioning
confidence: 99%
“…Of note, the presence of p-ANCA is suggested to be a marker for lupus symptoms in genetically susceptible individuals treated with minocycline for acne in relation with certain major histocompatibility complex class II genes including HLA-DR4, HLA-DR2 and HLA-DQB1, as observed in our patient [4]. Indeed, p-ANCA antibodies have been reported in druginduced autoimmune disorders such as hydralazine-induced lupus, and vasculitis and propylthiouracil-associated vasculitis [5][6][7]. The role of HLA-DR4 has been implicated in the development of hydralazine-induced lupus [8].…”
supporting
confidence: 63%
“…The occurrence of ANCA-associated vasculitis and glomerulonephritis has also been associated with hydralazine treatment (227)(228)(229), administered for hypertension. Again, MPO is the most important antigen that ANCA target in these patients (230,231). Some case reports suggested that, next to PTU and hydralazine, a variety of other medications, such as penicillamine, minocycline, allopurinol, sulfasalazine, levamisole, and thioridazine, were associated with ANCA-associated vasculitis (232-236); however, in larger studies, these hypotheses could not be confirmed (237).…”
Section: Pharmacologic Inductionmentioning
confidence: 99%